Isolation and identification of the causative agent of fowl cholera in Iraq and preparation of vaccines against the disease 1- Isolation of the causative agent of fowl cholera and study of it’s properties.: Hatem M .Mhanam , Ather K. Kassab , Esmail K. Shubber - Mhanam, Hatem M . (The Iraqi Journal of Veterinary Medicine, 2005)
It was possible to obtain 17 isolates of Pasteurella multocida frominfected laying chickens with fowl cholera. Three isolates were from the chronicphases of the naturally infected chickens and other fourteen were from the acutephases. The identification of these isolates was considered. Fifteen isolatesbelong to the sub species multocida and two isolates to gallicida, ten isolatesbelong to the SE-190 isolate and one to SE-077, while six isolates were notidentified. Twelve of the isolates have a capsule. The LD50s of these isolateswere varied. The results of sensitivity to antibacterial drugs revieled that allisolates were sensitive to Penicillin and resistance to Lincomycin with variousdegrees of sensitivity to other antibacterial drugs.